2010
DOI: 10.1210/jc.2009-1632
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary Excretion of 3-Methoxytyramine in Patients with Head and Neck Paragangliomas

Abstract: A substantial number of HNPGL patients have biochemically active tumors, reflected in increased excretion of 3-methoxytyramine, associated with increased dopamine excretion. Some patients only display increased excretion of 3-methoxytyramine, but not of other catecholamines or their metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 16 publications
5
61
1
1
Order By: Relevance
“…They typically have no or only a low production of catecholamines (Erickson et al 2001, van Duinen et al 2010) and commonly present as a slow-growing, painless cellular mass (DeLellis et al 2004). Consequently, many patients are non-symptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…They typically have no or only a low production of catecholamines (Erickson et al 2001, van Duinen et al 2010) and commonly present as a slow-growing, painless cellular mass (DeLellis et al 2004). Consequently, many patients are non-symptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that approximately 20% of the head and neck paragangliomas also produce significant amounts of catecholamines [6].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical markers like chromogranin, neuron-specific enolase and S100 are positive in the paragangliomas. MIB1 and p53 have been studied to assess their malignant potential [5,6].…”
Section: Case Historymentioning
confidence: 99%
“…Generally HNPGLs are parasympathetic in origin, and symptoms depend on the localization, tumour size, compression of surrounding structures and associated cranial nerve deficits. Between 4 and 30 per cent of HNPGLs secrete catecholamines4 5. HNPGLs can occur spontaneously or as part of a hereditary syndrome.…”
Section: Introductionmentioning
confidence: 99%